2004
DOI: 10.1093/petrology/egh027
|View full text |Cite
|
Sign up to set email alerts
|

Ultramafic Xenoliths from the Bearpaw Mountains, Montana, USA: Evidence for Multiple Metasomatic Events in the Lithospheric Mantle beneath the Wyoming Craton

Abstract: Ultramafic xenoliths in Eocene minettes of the Bearpaw Mountains volcanic field (Montana, USA), derived from the lower lithosphere of the Wyoming craton, can be divided based on textural criteria into tectonite and cumulate groups. The tectonites consist of strongly depleted spinel lherzolites, harzburgites and dunites. Although their mineralogical compositions are generally similar to those of spinel peridotites in off-craton settings, some contain pyroxenes and spinels that have unusually low Al 2 O 3 conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 68 publications
4
64
1
2
Order By: Relevance
“…This behaviour of Ca and Cr is not in agreement with other natural examples [61,70,71] and may imply percolation of a melt that was richer in Ca and Cr than the pyroxenite's precursors. Relic crystals with lobate boundaries and newly-formed, euhedral spinel crystals in Ol-orthopyroxenite show a range of Cr# resembling spinels from both marginal basins and boninitic basalts (Figure 4b-d).…”
Section: Origin Of Ol-orthopyroxenite and Websteritecontrasting
confidence: 67%
See 1 more Smart Citation
“…This behaviour of Ca and Cr is not in agreement with other natural examples [61,70,71] and may imply percolation of a melt that was richer in Ca and Cr than the pyroxenite's precursors. Relic crystals with lobate boundaries and newly-formed, euhedral spinel crystals in Ol-orthopyroxenite show a range of Cr# resembling spinels from both marginal basins and boninitic basalts (Figure 4b-d).…”
Section: Origin Of Ol-orthopyroxenite and Websteritecontrasting
confidence: 67%
“…Natural and experimental data reveal that Si-rich melts [56,57], or aqueous [58] or supercritical fluids [59] are released from the underlying subducted oceanic slab into the sub-arc region driving the dissolution of mantle olivine and the neoformation of pyroxenes and Al-phases in a range of pressures between 0.8 and 3.4 GPa [60][61][62][63][64][65][66][67][68]. Experimental results of Grant et al [69] at 800 MPa suggest that neoblasts of orthopyroxene and clinopyroxene form at a relatively narrow temperature range of around 800 to 900 ‱ C (with few exceptions up to 1100 ‱ C).…”
Section: Origin Of Ol-orthopyroxenite and Websteritementioning
confidence: 99%
“…However, the closely associated mela-aillikites fingerprint more reduced longterm isotopically enriched material within the Torngat UML magma source region and we have demonstrated that this component most likely resided in an old phlogopite-, K-richterite-, Ti-oxide-, and apatite-bearing assemblage. Such hydrous dominated, Ti-rich metasomatic assemblages are known from many cratons worldwide including the Wyoming and Churchill Provinces of Laurentia (Peterson and LeCheminant, 1993;Carlson and Irving, 1994;Downes et al, 2004). They form part of mantle-derived xenolith suites entrained by volatile-rich mafic/ultramafic magmas and appear to represent reaction products between hydrous alkaline melts of lamproitic composition and cratonic peridotite (Waters, 1987;Sweeney et al, 1993;Konzett et al, 1997;GrĂ©goire et al, 2002;Downes et al, 2004).…”
mentioning
confidence: 99%
“…Such hydrous dominated, Ti-rich metasomatic assemblages are known from many cratons worldwide including the Wyoming and Churchill Provinces of Laurentia (Peterson and LeCheminant, 1993;Carlson and Irving, 1994;Downes et al, 2004). They form part of mantle-derived xenolith suites entrained by volatile-rich mafic/ultramafic magmas and appear to represent reaction products between hydrous alkaline melts of lamproitic composition and cratonic peridotite (Waters, 1987;Sweeney et al, 1993;Konzett et al, 1997;GrĂ©goire et al, 2002;Downes et al, 2004). Rarely observed contact relationships indicate these assemblages form veins and striations within the deeper parts of cratonic lithosphere (Kramers et al, 1983;Waters and Erlank, 1988;Waters et al, 1989;Carlson and Irving, 1994;Rudnick et al, 1999).…”
mentioning
confidence: 99%
“…than Yb contents (3.6-7.2 t.ch.) [125]. The REE patterns of these phlogopites have the shape of lines with a gentle negative slope and are described by the values of (La/Yb) parameter in the range of 2.3-7.5 ( Fig.…”
Section: Micasmentioning
confidence: 93%